Effective one-pot chemoenzymatic cascade catalysis of biobased feedstock for synthesizing 2, 5-diformylfuran in a sustainable reaction system. (June 2023) - Li, Qing; Ma, Cui-Luan; He, Yu-Cai
Graphical abstract: Highlights: 2, 5-Diformylfuran (DFF) was prepared from biobased substrates in [BA][LA]–H2 O. Bread waste (50 g/L) was catalyzed to HMF (33% yield) in [BA][LA]–H2 O. Fructose (18 g/L) was catalyzed to HMF (92% yield) in [BA][LA]–H2 O. The prepared HMF was biologically oxidized to DFF by E. coli pRSFDuet-GOase. Bread waste and fructose were efficiently catalyzed to DFF. Abstract: 2, 5-Diformylfuran, which can be prepared via the oxidation of biobased HMF, has received considerable attention because of its potential applications in producing furan-based chemicals and functional materials, such as biofuels, polymers, fluorescent material, vitrimers, surfactants, antifungal agents and medicines. This work aimed to develop an efficient one-pot process for chemoenzymatic transformation of biobased substrate to 2, 5-diformylfuran with deep eutectic solvent (DES) Betaine:Lactic acid ([BA][LA]) catalyst and oxidase biocatalyst in [BA][LA]–H2 O. Using waste bread (50 g/L) and D -fructose (18.0 g/L) as feedstocks in [BA][LA]–H2 O (15:85, vol/vol), the yields of HMF were 32.8% (15 min) and 91.6% (90 min) at 150 °C, respectively. These prepared HMF could be biologically oxidized to 2, 5-diformylfuran by Escherichia coli pRSFDuet-GOase, achieving a productivity of 0.631 g 2, 5-diformylfuran/(g fructose) and 0.323 g 2, 5-diformylfuran/(g bread) after 6 h under the mild performance condition. This bioresourced intermediate 2, 5-diformylfuran was effectively synthesized from biobased feedstock in an environmentally-friendly system.